Vessel architecture in human knee cartilage in children: an in vivo susceptibility-weighted imaging study at 7 T - Kolb, Alexander (Eur Radiol, 2018)
OBJECTIVES: To evaluate the clinical feasibility of ultrahigh field 7-T SWI to visualize vessels and assess their density in the immature epiphyseal cartilage of human knee joints. METHODS: 7-T SWI of 12 knees (six healthy volunteers, six patients with osteochondral abnormalities; mean age 10.7 years; 3 female, 9 male) were analysed by two readers, classifying intracartilaginous vessel densities (IVD) in three grades (no vessels, low IVD and high IVD) in defined femoral, tibial and patellar zones. Differences between patients and volunteers, IVDs in different anatomic locations, differences between cartilage overlying osteochondral abnormalities and corresponding normal zones, and differences in age groups were analysed. RESULTS: Interrater reliability showed moderate agreement between the two readers (κ = 0.58, p < 0.001). The comparison of IVDs between patients and volunteers revealed no significant difference (p = 0.706). The difference between zones in the cartilage overlying osteochondral abnormalities to corresponding normal zones showed no significant difference (p = 0.564). IVDs were related to anatomic location, with decreased IVDs in loading areas (p = 0.003). IVD was age dependent, with more vessels present in the younger participants (p = 0.001). CONCLUSIONS: The use of SWI in conjunction with ultrahigh field MRI makes the in vivo visualization of vessels in the growing cartilage of humans feasible, providing insights into the role of the vessel network in acquired disturbances. KEY POINTS: • SWI facilitates in vivo visualization of vessels in the growing human cartilage. • Interrater reliability of the intracartilaginous vessel grading was moderate. • Intracartilaginous vessel densities are dependent on anatomical location and age. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00330-017-5290-1) contains supplementary material, which is available to authorized users.